The influences of economic progress, natural resources, and capitalization on financial development in the United States - Asif Raihan (Innovation and Green Development, 2024)
The significance of natural resources in facilitating financial activity is crucial in achieving a nation's sustainable economic advancement. This research directed to investigate the consequences of economic growth, rents of natural resources, and capitalization on financial development within the context of the United States (US). The investigation utilized the autoregressive distributed lag (ARDL) simulation, employing a dataset spanning the years 1970–2021. The outcome of the ARDL bound test supported the occurrence of cointegration midst the factors. The conclusions of the empirical analysis suggest that an outgrowth of 1% in natural resource rent, economic expansion, and capitalization would lead to a corresponding long-term increase of 0.30%, 0.26%, and 0.25% in financial development. Additionally, in the near term, these factors would contribute to an expansion of 0.22%, 0.22%, and 0.19% in financial development. Besides, the probe employed the Granger causality check to inspect the causal liaison concerning the factors. The investigation's results would stipulate visions for legislators in formulating a complete policy intended at augmenting the connection between finance and economy, with a specific focus on operating natural resources as a means to achieve sustainable development.